Harmonization Of Halal Certification In The IMT-GT Region: Opportunities, Challenges, And Integration Strategies - Moh. Nizar; Regiana Revilia (Utan Kayu Publishing, 2026)
The halal industry has attracted increasing global attention due to rising demand not only from Muslim-majority countries but also from non-Muslim nations, alongside the growing purchasing power of Muslim populations worldwide. In Southeast Asia, halal certification is managed through diverse institutional frameworks, ranging from government-led bodies in Singapore, Brunei, Cambodia, Vietnam, and Indonesia, to non-governmental organizations in the Philippines and Thailand. Indonesia established the Halal Product Assurance Agency (BPJPH) under Law No. 33/2014 to oversee national halal certification, while Malaysia’s Department of Islamic Development (JAKIM) has positioned the country as a global leader in halal governance and industry development. Thailand, despite its Buddhist majority, has advanced halal standardization through institutions such as the Halal Standard Institute and the Halal Science Centre. Within the Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT), where Muslims form a demographic majority, cooperation in the halal sector is strategically significant and relatively unimpeded by sociocultural barriers. Demand for halal products in the region—spanning food, pharmaceuticals, healthcare, cosmetics, logistics, tourism, and finance—is substantial, yet much of it is currently supplied by non-Muslim countries. Recognizing this, IMT-GT members have agreed to strengthen cooperation through three pillars: halal integrity, industry development, and branding and promotion. These efforts highlight the region’s ambition to establish itself as a global halal economic bloc, integrating certification, production, and market expansion within ASEAN and beyond.